TINJAUAN YURIDIS TERHADAP PENYALAHGUNAAN HAK UTAMA JALAN OLEH MASYARAKAT DITINJAU DARI UU NO 22 TAHUN 2009 TENTANG LALU LINTAS DAN ANGKUTAN JALAN - Iin Karmila (Journal of Law ( Jurnal Ilmu Hukum ), 2017)
ABSTRACTLaw No. 22 Year 2009 section 134 explains the primary rights of road users who prioritize or have the primary right to take precedence and must be escorted by the Indonesian National Police officers. Escort is done to reduce the potential for traffic accidents which are of course very dangerous to the convoy itself as well as other road users. But still many people who do not want to give way to vehicles that have the right of priority.This research uses research method with sociological juridical approach which is implemented in POLRESTA Samarinda city by using interview technique, and interviewing the community around writer area itself. The data obtained are primary and secondary data, and library research. Darta obtained kemudiaan analyzed descriptively.The results showed that many causes why people misuse the main right of the road is the lack of knowledge about the regulations. And how efforts and steps undertaken by the police officers of the Police RI to safeguard and guard against community and government activities as needed.  Key Words : misuse of the main right of the road